2003
DOI: 10.1088/0029-5515/43/12/007
|View full text |Cite
|
Sign up to set email alerts
|

Overview of recent Alcator C-Mod research

Abstract: Abstract.Research on the Alcator C-Mod tokamak [1] is focused on high particle-and power-density plasma regimes to understand particle and energy transport in the core, the dynamics of the H-mode pedestal, and scrape-off layer and divertor physics. The auxiliary heating is provided exclusively by RF waves, and both the physics and technology of RF heating and current drive are studied. The momentum which is manifested in strong toroidal rotation, in the absence of direct momentum input, has been shown to be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Indeed, although bidimensional arrays of probes are being increasingly popular in order to get snapshots of the full spatial structure of these structures 5,6 , most of the investigations are still being carried on through high-sampling-frequency point-wise measurements using Langmuir probes. The data are collected in the form of a time series, and then analyzed using various statistical tools.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although bidimensional arrays of probes are being increasingly popular in order to get snapshots of the full spatial structure of these structures 5,6 , most of the investigations are still being carried on through high-sampling-frequency point-wise measurements using Langmuir probes. The data are collected in the form of a time series, and then analyzed using various statistical tools.…”
Section: Introductionmentioning
confidence: 99%
“…Additional diagnostics have subsequently revealed that this type of plasma actually has a very flat density profile [56,57], so results from further simulations using R/L ne = 0.1 are shown in Fig. 3.…”
mentioning
confidence: 99%